2020
DOI: 10.3390/ijerph17030911
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Communication Measures Implemented During a School Tuberculosis Outbreak on Risk Perception among Parents and School Staff, Italy, 2019

Abstract: Risk perception has a significant impact on decisions people make when facing a threat: a mismatch between actual hazard and perceived risk can lead to inappropriate behaviours and suboptimal compliance to recommended public health measures. The present study was conducted in the aftermath of a tuberculosis (TB) outbreak that occurred in 2019 in a primary school in Italy. The aim was to evaluate the impact of communication measures implemented by local health authorities (including face-to-face meetings betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
52
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 20 publications
9
52
1
2
Order By: Relevance
“…Living with parents was another favorable factor against feeling anxious. Previous studies have indicated that the risk factors associated with emotional and anxiety disorders in adults include the death of parents in childhood, not living with parents, and parents' psychological problems and mental illnesses (Woodgate et al,2020;Gentili et al, 2020), which are consistent with the results of this study. Relatives or acquaintances being infected with COVID-19 was an independent risk factor in college students' anxiety about the epidemic, which might be related to the high contagiousness of the new coronavirus pneumonia (World Health Organization, 2020;Song et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Living with parents was another favorable factor against feeling anxious. Previous studies have indicated that the risk factors associated with emotional and anxiety disorders in adults include the death of parents in childhood, not living with parents, and parents' psychological problems and mental illnesses (Woodgate et al,2020;Gentili et al, 2020), which are consistent with the results of this study. Relatives or acquaintances being infected with COVID-19 was an independent risk factor in college students' anxiety about the epidemic, which might be related to the high contagiousness of the new coronavirus pneumonia (World Health Organization, 2020;Song et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…If dissemination is efficient, the public will receive accurate information and useful prevention suggestions in a timely manner. This method can help health authorities successfully manage this public health emergency [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several stressors have been identified as key factors affecting the students’ anxiety and psychological well-being: a parent or associate being infected by COVID-19; monetary issues and their effects on daily life; educational disruptions [ 11 ], effects of the disease on education and potential jobs [ 12 , 34 ]; and sensational broadcasts and inaccurate news reports [ 35 ]. Other stressors include students’ place of residence, family income stability [ 3 , 36 ], parents’ psychological status [ 37 ], reduced social interactions [ 38 ], increased number of new cases and affected provinces [ 13 ], and the imposition of travel bans affecting daily life [ 39 ].…”
Section: Introductionmentioning
confidence: 99%